Dwell‐time approach to ℒ 2 ‐induced gain analysis of discrete‐time switched systems subject to actuator saturation - Zhai, Shidong; Yang, Xiao‐Song (IET control theory & applications, 2013)
This study investigates ℒ 2 ‐induced gain from the input disturbance to output of discrete‐time switched linear systems subject to actuator saturation. With the state feedback gains adopted beforehand, the authors establish the linear matrix inequalities formulation which estimates the restricted ℒ 2 ‐induced gain for this class of switched systems by dwell‐time approach. Then the authors investigate the influence of parameter variations on the restricted ℒ 2 ‐induced gain, and present a state feedback design method for a fixed dwell time and an upper bound of restricted ℒ 2 ‐induced gain. In addition, the authors investigate the qualitative relationship between disturbances rejection capability and dwell time. A numerical example is provided to illustrate the effectiveness of our obtained results.